An Overview of ’Abd al-Wahhab al-Sha’rani’s Biography and Theological Thought - Mohamad Fuad, Mohamad Razif (Afkar: Jurnal Akidah dan Pemikiran Islam, 2025)
This study explores the intellectual and theological contributions of ʿAbd al-Wahhāb al-Shaʿrānī (d. 973/1565), a towering figure in post-Mamluk Egypt who bridged the realms of Sufism, Sunni orthodoxy, and legal scholarship. Moving beyond conventional portrayals of al-Shaʿrānī as merely a Sufi or jurist, the research highlights his role as a serious theologian. Through a critical analysis of his key works, al-Yawāqīt wa al-Jawāhir fī Bayān ʿAqāʾid al-Akābir and al-Qawāʿid al-Kashfiyyah al-Muwaḍḍiḥah li Maʿānī al-Ṣifāt al-Ilāhiyyah, the article demonstrates al-Shaʿrānī’s innovative synthesis of Ashʿarī-Māturīdī theology with spiritual insight. His theology articulates a delicate balance between tanzīh (divine transcendence) and tafwīḍ (textual fidelity), addressing complex issues such as the ambiguous Qurʾanic verses, anthropomorphism, divine attributes, and concepts like ḥulūl, ittiḥād, and waḥdat al-wujūd. The study argues that al-Shaʿrānī’s theological architecture not only reaffirmed Sunni orthodoxy but offered a compassionate intellectual framework capable of engaging both elite and popular religiosity. By situating al-Shaʿrānī within the broader canon of Sunni thought, this work calls for renewed scholarly attention to his contributions, particularly regarding the integration of theology, law, and mysticism in early modern Islam.